Demand for money in transition: evidence from China's disinflation - Aaron Mehrotra (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
We examine money demand in the Chinese economy during a period characterized by significant disinflation and outright deflation, coupled with strong output growth.Our study establishes a stable money demand system for broad money M2.Inflation affects the adjustment of the system towards equilibrium, and shocks to broad money are found to lead to higher inflation in the context of an impulse response analysis.The results provide support for the PBoC's policy of specifying intermediate targets for money growth. Importantly, our results suggest that movements in the nominal effective exchange rate should be taken into account in a successful implementation of such a policy.
URN:NBN:fi:bof-201408071965
Keywords: E31; E41; 330; Money demand; Deflation; China